Employee Silence: Commitment to Status Quo among Liberals and Conservatives with High Social Dominance - Sania Usmani; T. Ramayah (Asian Academy of Management Journal, 2023)
Many employees want to either retain their jobs or attain promotion. In doing so, they remain silent and conform to all the decisions taken by the top management. Most studies have treated the causes of this silence as unobserved intervening mechanisms and named them black boxes. The current study therefore, aims to explore those unobserved psychological characteristics of employees. More specifically, it examines the employee’s psychological ideology, namely liberalism and conservatism in affecting commitment to status quo mediated by employee silence and moderated by social dominance. This study proposes that employee ideologies (liberalism and conservatism) affect their voicing behaviour and ultimately their resistance or acceptance to the status quo. Data from 219 faculty members from different universities in Karachi, Pakistan was gathered. The study hypothesised that liberals will tend to voice their opinions and resist the managements status quo while conservatives tend not to voice their opinions and endorse status quo, and they accept management’s decision and will not question their actions. The results showed that liberals have an indirect relationship with silence, namely they do not remain silent. Additionally, silence had an indirect relationship with status quo. Even though they are silent it does not mean they endorse status quo. Further, it was found that silence mediates the relationship between liberals and commitment to status quo. It was also found that conservatives also endorsed status quo but there was no relationship between conservatives and silence. Further, silence did not mediate the relationship between conservatives and status quo. Moreover, social dominance orientation strengthens or moderates the relationship between silence and status quo.